Pengaruh Brisk Walking Exercise terhadap Daya Tahan Kardiorespirasi pada Penderita Hipertensi - Yuni Lestari, Ni Kadek; Intan Saraswati, Ni Luh Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Low cardiorespiratory endurance in young adults is associated with the development of cardiovascular disease risk factors in middle age. Training cardiovascular endurance and producing good endurance means that a person will not easily experience an increase in blood pressure because his fitness has been trained. Brisk Walking Exercise is a technique of fast walking for 30 minutes at a speed of 4-6 km/h. This exercise is quite effective for improving maximum heart rate capacity, stimulating muscle contraction, glycogen breakdown, and increased tissue oxygen. The purpose of this research is to determine the effect of brisk walking exercise on cardiorespiratory endurance in patients with hypertension. The research design is a pretest-posttest nonequivalent control group design. The analyses used are the wilcoxon test and the mann-whitney test. The research results obtained based on the wilcoxon test showed a p-value of 0,000 (0,05) in the treatment group, which indicates a significant difference in VO2 max values before and after the brisk walking exercise intervention. Meanwhile, the control group had a p-value of 0,011 which means there is no significant difference in VO2max values between the first measurement and the second measurement. Based on the Mann-Whitney test, the p-value 0,000 (0,05), which means there is an influence of brisk walking exercise on cardiorespiratory endurance (VO2max) in patients with hypertension. Brisk walking exercise can be an alternative complementary therapy that can increase cardiopulmonary functional capacity (VO2max) in hypertension sufferers.